Assisting MSMEs in Determining Optimal Prices Using Spreadsheet-Based Regression Analysis: Pendampingan UMKM dalam Menentukan Harga Optimal menggunakan Analisis Regresi berbasis Spreadsheet - Urwawuska Ladini; Zakiyatunnisa Al Mubarokah (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Student MSMEs often face economic vulnerability due to intuitive and unmeasured decision-making, particularly in setting selling prices that are both competitive and profitable in a price-sensitive market. This community service program aimed to strengthen the managerial capacity and data literacy of 30 student entrepreneurs at UIN Sulthan Thaha Saifuddin Jambi through spreadsheet-based regression analysis as an appropriate technology. The program employed a Participatory Action Research (PAR) approach through intensive training, hands-on mentoring using participants’ actual business data, and impact evaluation. The results showed a 110.1% increase in participants’ analytical competence after the intervention. Participants were able to move from intuition-based pricing toward more systematic and data-driven pricing decisions. In addition, the program encouraged more consistent sales data recording and improved participants’ ability to evaluate pricing alternatives based on demand patterns. This program contributed not only to strengthening technical and managerial skills but also to supporting the economic independence and business sustainability of student MSMEs.